RCEP Regional Comprehensive Economic Partnership An Emerging New World Power - Giudice Baca, Victor (2021)
The year 2020 will see the creation of   RCEP, a   Regional  Integration of  sixteen countries of Asia. GNP of  RCEP is  already superior to GNP  of  The  USA  and  European Union. One RCEP´s   member population (Indonesia) is 3.5 times bigger than Germany Population. RCEP Population consists of 3,500 millions  people, seven Times The European Population and ten Times The USA population. Asian Middle Class 2015 was already bigger than the middle class of USA and Europe. RCEP deserves a  special  atention of  Academicians ,Consulting firms, researchers of International Trade and business  leaders – since  Asia  is  the  first Market  of  Peru, Mercosur and Chile.